Female Archetypes in Panait Istrati’s Work: Array - Cernat-Mihai, Ionela (Journal of Danubian Studies and Research, 2021)
This study aims to highlight an important dimension of Panait Istrati’s work, the aspects of femininity in short stories and representative novels, created according to the exoticism of the Balkan environment evoked and the militant, idealistic nature of the writer, permanently open to the social problems of the beginning of the XXth century, interested in knowing the depths of the human being in general and otherness in particular. Sensitive to the affirmation and consolidation of the women’s emancipation movement, having the cult of friendship, freedom, beauty and truth, the narrative voices within Panait Istrati’s creation bring an unusual note by rewriting the archetypal patterns. Thus, the femme fatale, a tempting, passionate woman, but rejected by a hypocritical society, educates her children in the spirit of moral purity, even if life imposes other rules on her, an exception from a certain code of ethics. On the other hand, far from the well-known stereotype, the mother figure surprises through an atypical behavior, abandoning motherhood in favor of social commitment (the heroine/ outlaw woman) or adopting the shape of a brute that induces fear, anxiety or causes death of her own child. Regardless of the situation, the women in Panait Istrati's work represent the expression of the craving to escape, incessant search, freedom of spirit and external display of the good, humanistic values ​​- the purpose of any existence.